2019
DOI: 10.1186/s13030-019-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

Could emotional eating act as a mediator between sleep quality and food intake in female students?

Abstract: Background Poor sleep quality is associated with overeating and unhealthy eating. The aim of this study was to investigate if emotional eating could act as a mediator between poor sleep quality and energy/macronutrients intake. Methods This cross-sectional study was performed with 150 female school-age students, 13 to 19 years old, living in Tabriz, Iran. The Pittsburgh Sleep Quality Index (PSQI) and Emotional Eating Questionnaire (EEQ) were completed for data collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
2
12
1
2
Order By: Relevance
“…Before the study, the validity and reliability of the questionnaire were established. The Cronbach's alpha was 0.78 in the previous study [ 15 ] and 0.87 in this study.…”
Section: Methodssupporting
confidence: 63%
“…Before the study, the validity and reliability of the questionnaire were established. The Cronbach's alpha was 0.78 in the previous study [ 15 ] and 0.87 in this study.…”
Section: Methodssupporting
confidence: 63%
“…According to this study, sleep quality alone affected emotional eating in a rate of 8.3%. There are studies in literature before the pandemic showing that poor sleep quality was found to be associated with emotional eating [17][18][19] and unhealthy dietary behaviors [45], on the other hand, a study conducted on the women during the COVID-19 pandemic stated that sleep quality did not affect emotional eating [44].…”
Section: Discussionmentioning
confidence: 99%
“…The rst assumption is that the negative emotions motivate the individual to eat whilst the second assumption is that the act of eating lowers the intensity of negative emotions [15,16]. It is reported that there was a negative relationship between emotional eating and sleep quality [17][18][19] and positive relationship between emotional eating and anxiety and depression [20]. It is also reported that there is no direct relationship between emotional eating and fear of COVID-19, and that depression mediates the relationship between fear of COVID-19 and emotional eating [21].…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle çocukluk ve ergenlik döneminde uyku alışkanlığının kazanılması önemlidir. Çünkü bu dönemde kazanılan alışkanlıklar yaşam boyu devam eder (6). Çocuklarda, kaliteli ve yeterli uyku daha fazla dikkat, öğrenme yeteneği, hafıza, yaşam kalitesi, zihinsel ve fiziksel sağlık gibi olumlu sonuçlar ile ilişkilendirilmiştir (7).…”
unclassified
“…Uyku kalitesi ve süresinin azalması, çocuklarda hem besin alımının hem de yağ ve/veya rafine karbonhidrat içeren yiyecekleri tüketme eğiliminin artışına neden olmaktadır. Sağlıksız beslenme davranışlarının oluşması da obezite riskinin artışı ile sonuçlanmaktadır (6). Uyku süresinin azalması ile değişen metabolik hormonlar, kişide subjektif açlık ve iştah artışı ile sonuçlanmaktadır.…”
unclassified